The ecology and control of small hive beetles (Aethina tumida Murray) - Ellis, James Douglas (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2004)
The small hive beetle (Aethina tumida Murray) is an endemic scavenger in colonies of honey bee (Apis mellifera L.) subspecies inhabiting sub-Saharan Africa. The beetle only occasionally damages host colonies in its native range and such damage is usually restricted to weakened/diseased colonies or is associated with after absconding events due to behavioral resistance mechanisms of its host. The beetle has recently been introduced into North America and Australia where populations of managed subspecies of European honey bees have proven highly susceptible to beetle depredation. Beetles are able to reproduce in large numbers in European colonies and their larvae weaken colonies by eating honey, pollen, and bee brood. Further, adult and larval defecation is thought to promote the fermentation of honey and large populations of beetles can cause European colonies to abscond, both resulting in additional colony damage. The economic losses attributed to the beetle since its introduction into the United States have been estimated in millions of US dollars. Although beetles feed on foodstuffs found within colonies, experiments in vitro show that they can also complete entire life cycles on fruit. Regardless, they reproduce best on diets of honey, pollen, and bee brood. After feeding, beetle larvae exit the colony and burrow into the ground where they pupate. Neither soil type nor density affects a beetle's ability to successfully pupate. Instead, successful pupation appears to be closely tied to soil moisture. African subspecies of honey bees employ a complicated scheme of confinement (aggressive behavior toward and guarding of beetles) to limit beetle reproduction in a colony. Despite being confined away from food, adult beetles are able to solicit food and feed from the mouths of their honey bee guards. Remarkably, beetle-naïve European honey bees also confine beetles and this behavior is quantitatively similar to that in African bees. If confinement efforts fail, beetles access the combs where they feed and reproduce. Two modes of beetle oviposition in sealed bee brood have been identified. In the first mode, beetles bite holes in the cappings of cells and oviposit on the pupa contained within. In the second mode, beetles enter empty cells, bite a hole in the wall of the cell, and oviposit on the brood in the adjacent cell. Despite this, African bees detect and remove all of the infected brood (hygienic behavior). Similarly, European bees can detect and remove brood that has been oviposited on by beetles. Enhancing the removal rate of infected brood in European colonies through selective breeding may achieve genetic control of beetles. Additional avenues of control were tested for efficacy against beetles. Reducing colony entrances slowed beetle ingress but the efficacy of this method probably depends on other factors. Further, the mortality of beetle pupae was higher when contacting species of the fungus Aspergillus than when not, making biological control an option. Regardless, no control tested to date proved efficacious at the level needed by beekeepers so an integrated approach to controlling beetles remains preferred. The amalgamation of the data presented in this dissertation contributed to a discussion on the beetle's ecological niche, ability to impact honey bee colonies in ways never considered, and the ability to predict the beetle's spread and impact globally.
Keywords: Bee culture; Bee culture -- United States; Nitidulidae; Beetles -- Ecology; Beetles -- Control